“Prejudice, in fact, is ignorance”: accessibility actions proposal for the inclusion and permanence of employees with disabilities at a federal university in the countryside of Rio Grande do Sul - Giseli Rodrigues Wagner; Márcia Zampieri Grohmann (Avaliação: Revista da Avaliação da Educação Superior)
Abstract Law guarantees the entry of people with disabilities into the labor market. However, just making the vacancy possible does not guarantee the full inclusion and permanence of these people in the work environment. It is necessary that organizations be prepared and have in their culture the practice of accessibility actions that contribute to this process. This study aimed to propose accessibility actions according to the panorama of inclusion and permanence of servers with disabilities in a Federal University in the interior of Rio Grande do Sul. With a qualitative approach, of an exploratory nature, it was developed with content analysis of information from questionnaires with open questions, applied to 26 servers with disabilities at the Federal University of Santa Maria (UFSM). The results found indicate that UFSM is on the way to building an accessible University, but it still has barriers, mainly attitudinal, that can be minimized with proposed accessibility actions. In addition to understanding the panorama of inclusion and permanence of servers with disabilities in a Public University, the present study presents a proposal for accessibility actions that can provide better working conditions for people with disabilities. Also filling a gap in studies aimed at servers with disabilities and about actions that help in their real inclusion and permanence in the work environment.